Depressive symptoms associated with psychological correlates of physical activity and perceived helpfulness of intervention features - Hemmis, L.; De Vries, H.; Vandelanotte, C.; Short, C.; Duncan, M.; Burton, N.; Rebar, Amanda (Elsevier BV, 2015)
© 2015 Elsevier Ltd. All rights reserved. The anti-depressive benefits of physical activity are well-evidenced; however little is known about whether people with more frequent depressive symptoms have different psychological correlates of physical activity than people with less frequent symptoms, or whether special consideration is needed in targeting web-based physical activity interventions toward people with frequent depressive symptoms. An online cross-sectional survey was used to collect data from 511 adults (age = 45.99 ± 14.73 years). Two multiple regression analyses were conducted to test the relationship between frequency of depressive symptoms and (1) psychological correlates of physical activity (i.e., intentions, perceived behavioral control, affective attitudes, instrumental attitudes, and perceived physical activity effectiveness), and (2) perceived helpfulness of a variety of web-based physical activity intervention features. People with more frequent depressive symptoms had lower perceived behavioral control of physical activity (ß = -0.19), were more likely to report that goal-setting intervention tools (ß = 0.10) and personally-relevant information (ß = 0.09) would be helpful, and were less likely to report intervention features portraying information about how similar people are being regularly active as helpful (ß = -0.10) than those with less frequent symptoms. These findings highlight key components for designing web-based physical activity intervention content for people with depressive symptoms.